Cell-based phenotypic screens to identify modulators of sensitivity to N-methyl-N'-nitro-N-nitrosoguanidine - Pedley, N; Nicholas Michael Pedley (2011)
Defective DNA repair capacity has been shown to be a common feature of cancer, and loss of function mutations in 'stability' genes that normally maintain the integrity of the genome may prove a key rate-limiting step in carcinogenesis. Since even genetically unstable cells require some repair functionality to maintain viability, these cancers likely exhibit an over-reliance on other DNA repair pathways for survival. Therapeutically targeting backup repair processes in such tumours represents a novel means by which to achieve selective tumour toxicity. Full exploitation of these synthetic lethal interactions will require an in-depth knowledge of the genetic basis of DNA repair in combination with an armoury of small molecule inhibitors of cellular targets. To this end, we have designed, optimised and run two high-throughput cell-based screens to identify genes and small molecules that can modulate mismatch repair (MMR) activity. Key to these screening strategies are the resistance of cells with dysfunctional MMR to a range of cytotoxic drugs, including the alkylating agent N-methyl-N'-nitro-N-nitrosoguanidine (MNNG). By exploiting this MMR-dependent toxicity we have assayed for siRNA and small molecules that permit the survival of MNNG-treated MMR-proficient cells to levels comparable to MMR-deficient cells, and which therefore represent putative MMR modulating agents. A screen of 571 siRNA for gene depletions that reduce MNNG sensitivity by at least two population standard deviations identified 10 genes of potential interest, and included the four canonical MMR genes, MSH2 (2.87 ± 0.28 (Z ± SE)), MSH6 (4.87 ± 0.06), MLH1 (3.42 ± 0.43) and PMS2 (3.36 ± 0.44). TDG represented an unexpected hit that decreased MNNG sensitivity by 2.55 ± 0.04 population standard deviations. However, clonogenic survival experiments found TDG depletion to be contextual synthetic lethal within an MMR-null background when treated with MNNG, reducing HCT116 clonogenicity by 37% (p < 0.001). Moreover, TDG knockdown increased the number of 53 binding protein 1 (53bp1) foci in MMR-proficient cells by 40% and MMR–deficient cells by 27% following MNNG exposure (p < 0.001). Combined with a failure to replicate the primary screen result, the role for TDG in the response to MNNG could be explained solely through its established role as a member of the base excision repair pathway. A second screen of the NCI Diversity I and II small molecule libraries (n=1786) was conducted to identify putative MMR inhibitors. Subsequent analysis revealed NSC197049 to increase cellular viability of MNNG treated cells by 3.60±0.32 population standard deviations and was successfully validated as a hit. Co-treatment of NSC197049 with MNNG conferred dose-dependent chemoprotection independently of MMR status and cell line, an effect that was lost if NSC197049 was pre- or post-treated. The protection was associated with a reduction in MNNG-dependent 53bp1 foci of 60% in MMR proficient cells and 15% in MMR deficient cells (p < 0.001), together with a marked reduction of > 80% in subG1 content at 48 hours post-MNNG that was independent of MMR status. Interestingly, the characteristic G2/M arrest of MNNG-treated MMR-proficient cells remained intact (~40% arrested). Taken together, these observations are not consistent with NSC197049 acting as an inhibitor of MMR. Dithiolthiones have been described as chemoprotective agents that induce antioxidant defences, whilst we have found NSC197049 phenocopies known antioxidants ascorbic acid and glutathione in protecting against MNNG-induced toxicity. NSC197049 may therefore act by bolstering cellular antioxidant defences. The precise mechanism may be novel, since the proto-typical dithiolthione, Oltipraz, failed to be protective in this study. In summary, we have confirmed that MMR is the primary determinant of MNNG sensitivity, and found that TDG is unlikely to be involved in MMR. We have also identified a novel chemoprotective small molecule that is unlikely to represent an MMR inhibitor, but that might be useful in cancer chemoprevention.